2019
DOI: 10.5152/tud.2018.92072
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of urologic complications in obstetrics and gynecology: 13 years’ experience from a tertiary referral center

Abstract: Objective:To analyze the patterns of presentation and management for urologic complications of obstetrics and gynecology in the form of genitourinary fistulas at a tertiary referral center and highlight the social issues associated with them. Material and methods:We conducted this retrospective study analyzing 311 patients with genitourinary fistulas after obstetric and gynecologic surgeries between January 2005 and January 2018. We recorded the patients' characteristics and area of residence and then analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…13,21,36,46,47,[53][54][55] All retrospective nonrandomized comparative studies (30 studies) and prospective nonrandomized comparative studies (5 studies) were considered high risk of bias because these studies evaluated interventions designated by surgeon preference, varied in their follow-up, provided limited information on evaluation of cure, and did not control for confounding factors. 14,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,[39][40][41][42][43][44][45]48,49,51,52,[56][57][58] One comparative study, by Geisler et al, 25 reported preoperative assessment of the fistula for surgical planning. This prospective nonrandomized comparative study (N553) describes the use of phenazopyridine given preoperatively to identify fistula tracts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…13,21,36,46,47,[53][54][55] All retrospective nonrandomized comparative studies (30 studies) and prospective nonrandomized comparative studies (5 studies) were considered high risk of bias because these studies evaluated interventions designated by surgeon preference, varied in their follow-up, provided limited information on evaluation of cure, and did not control for confounding factors. 14,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,[39][40][41][42][43][44][45]48,49,51,52,[56][57][58] One comparative study, by Geisler et al, 25 reported preoperative assessment of the fistula for surgical planning. This prospective nonrandomized comparative study (N553) describes the use of phenazopyridine given preoperatively to identify fistula tracts.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluated domains included route of repair and the use of flaps, trimming, layered closure, antibiotics, fascial sling, and fibrin glue (Table 1). 13,14,[16][17][18][20][21][22][23][24][27][28][29][30][31][33][34][35][36][37][40][41][42][44][45][46][48][49][50][51][52][53][56][57][58] Seventeen studies were identified (two prospective nonrandomized comparative studies, 15 retrospective nonrandomized comparative studies) that evaluated vaginal compared with abdominal (through laparotomy) routes of vesicovaginal fistula repair (N51,143). 14,16,18,20,24,29,30,33,35,37,40,41,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations